Problems of Learning Arabic in Elementary School - Makfiro, Nikmatul; Rosyada, Amrina; Imtiyazuha, Imtiyazuha; Kader, Muhammed Yahya (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
Arabic language learning plays an important role in Islamic-based educational institutions in Indonesia because it is closely related to religious practices and Islamic knowledge. However, the implementation of Arabic language learning at the elementary school level often faces various challenges that affect the effectiveness of the learning process. This study aims to identify the challenges encountered in Arabic language learning at the elementary level and to analyze the strategies used by teachers to address these challenges. This research employed a qualitative descriptive approach and was conducted at SDIT Robbani Singosari Malang. Data were collected through interviews and classroom observations involving an Arabic language teacher. The data were analyzed using qualitative data analysis techniques including data reduction, data display, and conclusion drawing. The findings reveal that the challenges in Arabic language learning arise from both linguistic and non-linguistic factors, such as students’ ability to read Hijaiyah letters, differences in educational background, and low learning interest. To overcome these challenges, teachers apply several strategies including the singing method, peer tutoring, and the use of pocket dictionaries to support vocabulary learning. These strategies help create a more engaging learning environment and improve students’ participation in the classroom. The results of this study highlight the importance of varied and interactive teaching methods to enhance the effectiveness of Arabic language learning at the elementary school level.